2012
DOI: 10.1007/s00520-012-1646-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of high score patient-reported barriers to controlling cancer pain: a preliminary report

Abstract: Purpose Pain is one of the most common and devastating symptoms in cancer patients, and misunderstandings on the patient’s part can cause major obstacles in pain management. Method We evaluated factors associated with patient’s high barrier score to managing cancer-associated pain by having 201 patients complete the Korean Barriers Questionnaire II, the Brief Pain Inventory—Korean, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30, and the Korean Beck Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
(49 reference statements)
1
20
1
Order By: Relevance
“…Our previous study, which looked at a population of Korean cancer patients, found an association between high barriers scores in cancer pain management and depression; 17 however, the current study found no significant association in this respect (see Table 5). This discrepancy might be explained by the fact that these two studies each used different tools to measure depression: the Beck Depression Inventory for the Korean population and the depression section of the ESAS for the North American population.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…Our previous study, which looked at a population of Korean cancer patients, found an association between high barriers scores in cancer pain management and depression; 17 however, the current study found no significant association in this respect (see Table 5). This discrepancy might be explained by the fact that these two studies each used different tools to measure depression: the Beck Depression Inventory for the Korean population and the depression section of the ESAS for the North American population.…”
contrasting
confidence: 51%
“…Those higher scores are consistent with the results of our previous study, which focused on Korean cancer patients. 17 Comparing to the Korean study, which was conducted in an oncology clinic, 17 differences in results might be attributed to differences in the study populations, such as in race, clinical characteristics, and medical services received, or to the relatively lower pain management barrier scores in the current study (see Table 6). However, the most important difference might be the increased time that the palliative care team spends communicating with patients in a palliative care clinic compared with health care provider-patient communication in regular oncology clinics, where the discussion must focus on cancer management and planning in addition to pain and symptom management.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…31,44 A large recent national study 17 did not find any association between provider-assessed patient emotional distress and pain in a diverse sample of cancer patients. However, some evidence suggests that providers may underestimate depression or emotional distress among cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…9 Depression is also found to be a significant barrier to manage pain, underscoring the importance of managing depression in order to improve pain. 10 According to the National Comprehensive Cancer Network, distress is an "unpleasant experience of a mental, physical, social, or spiritual nature." It can affect the way an individual thinks, feels, or acts and can make coping more difficult.…”
Section: Psychological Painmentioning
confidence: 99%